Assessing the Islamic values in the halal supply chain of the poultry industry / Emi Normalina Omar - Omar, Emi Normalina (2017)
The values in our daily life are important as the values play a role in influencing our principles and behaviours, and positive values could create good behaviour and a happy living. Thus, values in Islam are essential as those act as a guide for Muslims to be the good believers and capable in forming the better societies. These values are based on the Shariah principles which can be found in the Holy Qur'an, which dominantly enacted as the main reference of foundation for Muslims in present time and the Hereafter. Occasionally, Muslims do not realise that the good things that they do in their daily activities are considered as good values from the Islamic perspective, i.e. Islamic values. The present business environment of the food supply chain, particularly the poultry industry has been chosen in this study due to the fact of highest food consumption of Malaysian in poultry and poultry based products. This study found that research which assessing the Islamic values and halal supply chain has received relatively little attention in the literature. Therefore, this study attempts to fill this void by assessing the Islamic values in the halal supply chain of the poultry industry. This study focuses on the existing poultry supply chain by underlying Islamic values that exist and might capable to assist the implementation of halal supply chain as to be resilience and sustainable in the future. By using a qualitative approach, the main data was collected from in-depth interviews of three case studies. The three case studies are interrelated in the poultry supply chain as the first case is focused on the initial stage of supply chain i.e. farm, while the second case emphasises on five slaughterhouses. The final and third case focuses on the final stage of the supply chain which is retailers' premises. The study determined the fundamental of Islamic values that emerge throughout the entire halal supply chain of the poultry industry. The study then highlights the importance of the Islamic values in the halal supply chain. A model was formed based on eleven dimensions, namely accountability, awareness, commitment, competency, dedication, efficiency, kindness, knowledge, sincerity, spiritual well-being, and trustworthiness. The research contributes to the literature of Islamic values as well as the supply chain management literature by supporting the ethical theory of Al-Ghazali. This study proposed three new dimensions, namely awareness, commitment and competency dimensions in assessing the halal supply chain that is incorporated in the newly proposed assessment Islamic values model.